Effects of Bacillus licheniformis on the water quality, growth performance and bacterial community in Penaeus vannamei aquaculture system - Zheng, Yi; Wu, Yingzi; Tang, Shuling; Li, Junpeng; Fan, Lingyu; He, Wenjin (Frontiers in Microbiology, 2025)
IntroductionThis study investigated the effects of Bacillus licheniformis on the water quality, growth performance and bacterial community in Penaeus vannamei aquaculture system. The objective was to elucidate the impact of B. licheniformis on P. vannamei aquaculture from a microbial ecological perspective. This research provided valuable theoretical support for the practical application of B. licheniformis in improving aquaculture practices for P. vannamei.MethodsThe design of the aquaculture experiment comprised two groups: a control group (CK) fed a basal diet and a treatment group (PB) was fed the same diet with addition of B. licheniformis (5 × 104 CFU/mL) into the water every 5 days. These groups were systematically evaluated through comprehensive water quality analyses, including pH, ammonia nitrogen, nitrite nitrogen, and Vibrio counts, as well as growth performance assessments such as length, weight, survival rate, yield, and feed conversion ratio (FCR). Additionally, high-throughput sequencing technology was employed to analyze changes in bacterial community structures in both the aquaculture water and the shrimp intestines.ResultsThe results demonstrated that B. licheniformis significantly improved water quality, promoted shrimp growth, and altered the bacterial community structure: (1) B. licheniformis significantly reduced the concentrations of ammonia nitrogen, nitrite nitrogen, and pathogenic Vibrio counts in the later stages of cultivation (P < 0.05), while significantly promoting shrimp growth; (2) The addition of B. licheniformis increased the diversity and richness of bacteria both in the water and shrimp intestinal tracts, leading to significant changes in bacterial community structure. It also enhanced beneficial bacterial genera such as Gemmobacter, Paracoccus, and Bacillus in the water, while concurrently reducing the potential pathogenic Flavobacterium in the shrimp intestinal tract; (3) The dominant bacterial populations were significantly affected in both water and shrimp intestinal samples. In water, Aurantimicrobium was the predominant genus in both groups, with the PB group showing a notably lower relative abundance. In the shrimp intestines, the CK group was dominated by Gemmobacter and Fluviicola, while Aurantimicrobium prevailed in the PB group. In conclusion, the study revealed the potential of B. licheniformis in shrimp aquaculture by improving water quality, promoting shrimp growth, and modulating bacterial community structure.DiscussionThis study demonstrated that B. licheniformis significantly improved water quality and shrimp growth performance in P. vannamei aquaculture. It effectively reduced pH, ammonia and nitrite levels, while also decreasing Vibrio counts, which are critical for disease control. B. licheniformis enhanced microbial diversity in both aquaculture water and shrimp intestines, promoting the abundance of beneficial genera, while reducing potential pathogens. The alteration in bacterial community structure suggests that B. licheniformis plays a pivotal role in maintaining a healthy microbial ecosystem, enhancing shrimp health and growth, and providing an environmentally sustainable alternative to antibiotics in aquaculture practices. These findings underscore the potential of B. licheniformis for improving P. vannamei aquaculture systems.